Laparoscopic and open transhiatal oesophagectomy for corrosive stricture of the oesophagus: An experience - Vaibhav Kumar Varshney; Hirdaya H Nag; B G Vageesh (Journal of Minimal Access Surgery, 2018)
Background: Oesophagectomy for corrosive stricture of the oesophagus (CSE) is rarely performed due to high risk of iatrogenic complications. The aims of this study were to review our experience of transhiatal oesophagectomy (THE) in patients with CSE as well as to compare results of open and laparoscopic methods. Materials and Methods: This is a retrospective analysis of prospectively maintained data of patients with CSE who underwent open transhiatal oesophagectomy (OTE) or laparoscopic-assisted transhiatal oesophagectomy (LATE) by a single surgical team from 2012 to 2016. All study patients had either failed endoscopic dilatation or had a long stricture which was not amenable to endoscopic dilatation. Results: Totally, 35 patients were included in the study, of which 19 (54.3%) were female. OTE was performed in 20 (57%) patients, and LATE was performed in 15 (43%) patients. Gastric and colonic conduits were used in 23 (65.7%) and 10 (34.3%) patients, respectively. Demographic and clinical parameters were comparable between LATE and OTE groups (P > 0.05). Median intra-operative blood loss, post-operative requirement of analgesic and hospital stay were lower in LATE group (P ≤ 0.05). There was no hospital mortality (30 days), but three patients (8.6%) died during a median follow-up of 36 months. Conclusion: THE is a safe procedure for patients with CSE, and LATE may be an alternative approach in selected patients.